Demografski potencial hribovskih kmetij na Dravskem Pohorju - Kerbler, Boštjan Kefo (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
In the article is represented and evaluated the demographic potential of mountain farms on Dravsko Pohorje. The characteristics of socio-economic structure, depopulation, deagrarization, demographic vitality, productiveness,and succession continuity of mountain farms are described. The results indicate that demographic vitality is weakened due to permanent emigration of young population, as well as succession continuity on many farms is not assured.
Keywords: Pohorje; hribovska območja; hribovske kmetije; prebivalstvo; demografski razvoj; razvojna strategija